Legibility based on differentiation of characters: A review of empirical findings fundamental for the type design practice - Nedeljković, Uroš; Puškarević, Irma; Banjanin, Bojan; Pinćjer, Ivan (Journal of Graphic Engineering and Design, 2023)
The purpose of the study was to analyse findings in the field of the pattern recognition, visual word recognition and legibility ofgraphemes. The paper focuses on the most significant findings for comprehending the function of the graphemic characteristic during word and letter recognition. The aim of the study, as it is presented in the discussion part, was to analyse the factors which have induced inconsistencies between the findings acquired by confusion matrix, as well as to compare findings which continually lead type scholars to progression.